Knowledge Management dan Kemas Ulang Informasi di Perpustakaan Perguruan Tinggi : Hambatan dan Peluang Perpustakaan Masa Depan - Kardi Kardi (Pustakaloka, 2009)
The outburst of information triggers the difficulty of information users to selct and gain infortmation which is appropriate with their necessities.  The user tipically demand a prepared information service quickly, accurately and easily.